2016
DOI: 10.1177/0160323x15624474
|View full text |Cite
|
Sign up to set email alerts
|

The Absence of Social Equity Measurement in Municipal Service Privatization

Abstract: As privatization of municipal service becomes commonplace, empirical evidence is necessary to ensure that services delivered are equitable and responsive to all citizens. This article looks specifically at social equity measures in municipal service privatization. Using panel data analysis with survey data from a large southwest city, it examines how privatization affects citizens’ reported quality ratings of solid waste service in communities of different ethnicities. The findings show that customers of priva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…An analysis of Swedish municipalities found that higher levels of outsourcing were associated with lower levels of citizen satisfaction (Dahlström, Nistotskaya, and Tyrberg, 2018). Similarly, in an analysis of the municipal solid waste collection, customer satisfaction data results showed that privately delivered services generally reported lower ratings than publicly delivered services and in Latino concentrated areas, these ratings were significantly lower (Wang and McFadden, 2016). In contrast, as study of Norwegian municipalities, implied that contracting increases service quality and creates a service-oriented culture increasing satisfaction (Holum, 2016).…”
Section: Citizen Satisfaction and Contracting Outmentioning
confidence: 96%
“…An analysis of Swedish municipalities found that higher levels of outsourcing were associated with lower levels of citizen satisfaction (Dahlström, Nistotskaya, and Tyrberg, 2018). Similarly, in an analysis of the municipal solid waste collection, customer satisfaction data results showed that privately delivered services generally reported lower ratings than publicly delivered services and in Latino concentrated areas, these ratings were significantly lower (Wang and McFadden, 2016). In contrast, as study of Norwegian municipalities, implied that contracting increases service quality and creates a service-oriented culture increasing satisfaction (Holum, 2016).…”
Section: Citizen Satisfaction and Contracting Outmentioning
confidence: 96%
“…McCandless et al (2022) employ the framework to understand the implications of diversity, equity, and inclusion in public administration with implications across the world. Other public administration literature focuses on one or more of the four dimensions of social equity: procedural fairness (Ruder & Woods, 2020), access (Liang et al, 2020; Nisar, 2018), quality (Wang & McFadden, 2016), or outcomes (Blessett, 2020; Gaynor & Wilson, 2020; Wright & Merritt, 2020). Others call attention to social and racial equity in policy delivery and administration (Fay et al, 2021; Maynard‐Moody & Musheno, 2012; Rubin & Bartle, 2021), provision of information affecting their communities (Fusi et al, 2023), co‐production of knowledge (Schwoerer et al, 2022), and curriculum (Benenson et al, 2022; Berry‐James et al, 2021; Dantzler & Yang‐Clayton, 2022; Gaynor & Lopez‐Littleton, 2022).…”
Section: Social Equity Frameworkmentioning
confidence: 99%
“…It follows that research determining “what works,” and theory development using a cognitive approach, must first be consistent with the core tenet of social equity for it to have applicability. If an evidence-based policy or decision is inconsistent with the tenet of social equity, in cannot be deemed effective in a humanity-based approach to PA. Related, it also speaks to the need for continued study of how to measure and advance social equity in practice (Guy & McCandless, 2012; Jos, 2016; Wang & McFadden, 2016).…”
Section: Value Conflicts In Pamentioning
confidence: 99%